The city school resource pack mathematics term 1 nursery (The City School Lahore, 2016)
This resource pack emphasizes key concepts such as number recognition, basic operations, patterns, and measurement through engaging activities and colorful illustrations. Designed to stimulate curiosity and promote critical thinking, the workbook encourages children to explore mathematical ideas in a fun and interactive manner. By providing a strong foundation in early mathematics, it prepares students for future academic challenges and fosters a lifelong love for learning in the subject.